A study on assessment of awareness on generic drugs among doctors in a tertiary care teaching hospital in north India - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2018)
Background: The assessment of doctors’ perceptions and understanding about generic medicines may help in recognizing the key areas which may act as hurdle to mass scale use of generics. The primary objective of this study was to explore the knowledge, attitude, and practice (KAP) of doctors toward generic medicines. Methods: A cross-sectional study was carried out using a pretested questionnaire in a tertiary care teaching hospital of Jammu (J and K). The questionnaire was designed to assess the KAP about generic medicines. The doctors working in this institute during the study period were included. Data was compiled and analysed using online website, http://www.graphpad.com. P-values of < 0.05 were considered to indicate statistical significance. Results: A 62.9% doctors agreed to the fact that generic medicines were intended to be interchangeable with a branded drug (p=0.0139). Among the doctors, 77.5% were aware that generic drug manufacturers need to conduct studies to show bioequivalence between the generic medicine and their branded counterparts (p =0.0001). 88.8% of the doctors agreed that importance of generic medicines should be taught in early part of internship. 80.9% doctors did not think that switching a patient from a brand-name to generic drug may change the outcome of the therapy (p <0.0001). Conclusion: The present study showed that a good percentage of doctors were well aware of generic medicines’ usage. However due to concerns expressed by a certain fraction of participants, further work is needed on how interventions for medical professionals and for the public can lead to increase in the awareness and acceptability of generic medicines.